2014
DOI: 10.1002/adma.201400243
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement in Photocatalytic Reduction of Water to Hydrogen by Au/Cu2ZnSnS4 Nanostructure

Abstract: Enhanced photocatalytic activities by Au core Novel Au/Cu2 ZnSnS4 core/shell nanoparticles (NPs) are synthesized for the first time via wet chemistry approach. The insertion of Au core into CZTS NPs dramatically enhances light absorption due to surface plasmon resonance effect, especially in the Vis-NIR region. Au/CZTS core/shell NPs show much higher photocatalytic activities for hydrogen evolution compared with other CZTS nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
111
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(119 citation statements)
references
References 23 publications
6
111
0
Order By: Relevance
“…Among them, In 4 Pb x Sn y Se 3 is a promising mid-temperature thermoelectric material candidate [6]; Ba 7 Sn 5 S 15 demonstrates the coexistence of Sn 2 S 3 trigonal-bipyramids and SnS 4 tetrahedra and shows a strong SHG effect [5]; Ba 6 Sn 6 Se 13 has mixed valent Sn 2+ and Sn 4+ cations in 3-fold, 4-fold, and 5-fold coordination environments respectively and shows a moderate NLO effect [7]. In the meanwhile, Cu 2 ZnSnS 4 , Cu 2 FeSnS 4 and Ag 2 ZnSnS 4 have attracted great interest for their photovoltaic and H 2 production performance [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Among them, In 4 Pb x Sn y Se 3 is a promising mid-temperature thermoelectric material candidate [6]; Ba 7 Sn 5 S 15 demonstrates the coexistence of Sn 2 S 3 trigonal-bipyramids and SnS 4 tetrahedra and shows a strong SHG effect [5]; Ba 6 Sn 6 Se 13 has mixed valent Sn 2+ and Sn 4+ cations in 3-fold, 4-fold, and 5-fold coordination environments respectively and shows a moderate NLO effect [7]. In the meanwhile, Cu 2 ZnSnS 4 , Cu 2 FeSnS 4 and Ag 2 ZnSnS 4 have attracted great interest for their photovoltaic and H 2 production performance [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…It is thought that ethylenediamine plays an important role in the chalcogenide phase transition processes between the tetragonal and hexagonal structures [11,12]. Recently, W-CZTS has been used as a photocatalyst to fabricate CZTS-metal (Au or Pt) structure [6,13,14]. It is demonstrated that the structure is capable of enhancing photocatalytic activity towards the degradation of pollutions, but the noble metal would increase the cost.…”
Section: Introductionmentioning
confidence: 98%
“…Various semiconductors, such as metal oxides, sulfides, oxynitrides, and organic polymers, have been specially designed to develop highly efficient and stable photocatalytic hydrogen production systems [5][6][7][8][9][10]. Among various metal oxide semiconductor photocatalysts, nanostructured zinc oxide has been proven to be a suitable candidate for solar-to-H 2 conversion owing to its low-cost, nontoxicity, excellent stability and abundance [11,12].…”
Section: Introductionmentioning
confidence: 99%